Evaluation of drinking water supplementation of two different herbal blends on productive performance and immune responses of broiler chickens - Amir Hossein Alizadeh-Ghamsari; Seyed Adel Moftakharzadeh; Seyed Abdullah Hosseini (Acta Scientiarum: Animal Sciences)
This study was carried out to evaluate the effects of herbal mixture on the growth performance, intestinal microbial population, and immune responses of broiler chickens. In all, 600 day-old as-hatched Ross 308 broiler chickens were assigned in a completely randomized design with four treatments, five replicates, and 30 birds in each replicate. The four treatments were: the control group (not treated) and, the second group received 1 mL L-1 herbal solutions (Bioherbal®), and two other groups were received 16.6, and 33.3 mL L-1 commercial herbal solutions (Orex®), respectively. Results showed that while water supplementation of the herbal mixture had no significant effect on feed intake (FI), body weight (BW), and feed conversion ratio (FCR) of broiler chickens (p > 0.05), the productive efficiency index (PEI) improved by dietary inclusion of herbal blend at 33.3 mL L-1 (p < 0.05). Furthermore, the lactobacilli population increased and E. coli population was reduced by both herbal mixture addition (p < 0.05). The application of both Herbal growth promoters (Orex® and Bioherbal®) boosted cellular and humoral immunity and decreased the heterophil-to-lymphocyte ratio (p < 0.05). The present study indicated the positive effect of Orex® addition to water at both concentrations (16.6 or 33.3 mL L-1) on livability, PEI, ileal microbial populations, and immune system function.